The use of classroom environment improvement plans in an attempt to change aspects of teacher interpersonal behaviour and the science laboratory learning environment in order to improve student outcomes - Brownson, Deborah Ann (Curtin University, 2006)
The learning environment has been the focus of considerable educational research over a long period of time. The study reported in this thesis utilises the perceptions of 208 junior science students from a North Queensland state secondary school to inform classroom environment improvement plans developed and implemented by their teachers' in an attempt to improve the cognitive and attitudinal outcomes of the students. The five stage process on which the study is based combines theory and practice in providing the participating teachers with a structured means of bringing about change in their classrooms. Students' perceptions of actual and preferred teacher interpersonal behaviour and the laboratory learning environment are measured using the QTI and SLEI respectively. Particular aspects of teacher interpersonal behaviour and the laboratory learning environment are targeted for change through the classroom environment improvement plans. The study identified which aspects of the learning environment had changed after a period of intervention. It also identified associations between students' perceptions of aspects of their laboratory learning environment and attitudinal outcomes as well as associations between teacher interpersonal behaviours and attitudinal outcomes. While no direct associations were found between aspects of the laboratory learning environment or teacher interpersonal behaviours and cognitive outcomes, students' cognitive outcomes did improve over the duration of the study thus supporting a previously established link between student attitudes and cognitive outcomes.